The Effectiveness of MPI BeWe to Improve the Learning Quality of Prospective Elementary School Teachers in the Elementary Teacher Education Study Program (PGSD) FKIP Unsri - Apit Fathurohman; Esti Susiloningsih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
The Web-Based Interactive Learning Multimedia (MPI BeWe) has been successfully developed for students of the Elementary School Teacher Education Study Program (PGSD) for the subject of Science Basic Concepts. 1. The problem raised in this research is how to develop Web-Based Interactive Learning Multimedia (MPI BeWe) to improve the quality of learning for elementary school teacher candidates in the PGSD Study Program FKIP Unsri. This study aims to improve the quality of the learning process for the Basic Science Concept course in the Elementary School Teacher Education Study Program (PGSD). The method used in this research is a quasi-experimental method. The research design used is the One-Group Pretest-Posttest Design. The sampling technique used is the Cluster Random Sampling (CRS) technique. The instruments used in this study were pretest and posttest with multiple choice techniques, observation sheets, and questionnaires in the form of student responses to learning using web-based interactive multimedia learning (MPI BeWe). The application of web-based interactive multimedia learning (MPI BeWe) shows the effectiveness of learning for first semester students of the PGSD study program. This can be seen from the increase in the percentage results of the average value of the pretest and posttest results and the increase in the results of the average gain g>. Thus, it can be concluded that there is an effective application of web-based interactive learning multimedia (MPI BeWe).